Uncovering the Potential of STEM-Based Biotechnology Materials Biology Learning: A Systematic Literature Review - Ngade Wantara; Slamet Suyanto; Necta Ayu Cahyanti; Tatag Bagus Putra Prakarsa (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2025)
The Science, Technology, Engineering, and Mathematics (STEM) approach has become a key paradigm for improving the quality of 21st-century science education, including biology learning. Biotechnology material, which has broad applications in daily life, can be taught more effectively through STEM integration. This study aims to examine the potential of STEM-based biotechnology learning through a Systematic Literature Review (SLR). The review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to ensure a transparent and systematic process. A total of 50 articles were initially identified from databases such as Google Scholar, Scopus, and Web of Science using the Publish or Perish application. After screening and eligibility assessment, 10 relevant articles were included in the final analysis. The results indicate that STEM-based biotechnology learning enhances students’ conceptual understanding, promotes critical thinking, and fosters innovation. However, its implementation still faces challenges, including limited infrastructure, insufficient teacher training, and lack of supporting teaching materials. In conclusion, STEM-based biotechnology learning has strong potential to be integrated into Indonesia’s biology curriculum but requires policy support, teacher capacity building, and resource development. This review provides a foundation for developing more effective implementation strategies.